2015
DOI: 10.4236/jwarp.2015.79061
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Variations in Water Physicochemical Quality of Coastal Potou Lagoon (Côte d’Ivoire, Western Africa)

Abstract: The study investigates the seasonal and spatial variations in water quality parameters at four different locations along Potou lagoon for seventeen consecutive months. In order to explore spatial variation among different stations and seasonal changes, no parametric test of ANOVA was used to compare the mean values of the tested parameters for all the different sampling sites and seasons. Seasonal observations on water quality parameters and chlorophyll-a in Potou coastal lagoon revealed that the coastal water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
3
2
Order By: Relevance
“…The recorded low values at A4 and I6 (<5 µg/L ) could be attributed to turbidity of the water, which minimized light penetration and eventually led to low concentration of phytoplankton biomass at the two stations. In comparison to other stations, the mean concentrations of chlorophyll-a of our study area (Table 2) is lower to the reported values of Marthe et al, (2015) who recorded 19.2µg/L at Coastal Potou Lagoon, Côte d'Ivoire.…”
Section: Resultscontrasting
confidence: 94%
“…The recorded low values at A4 and I6 (<5 µg/L ) could be attributed to turbidity of the water, which minimized light penetration and eventually led to low concentration of phytoplankton biomass at the two stations. In comparison to other stations, the mean concentrations of chlorophyll-a of our study area (Table 2) is lower to the reported values of Marthe et al, (2015) who recorded 19.2µg/L at Coastal Potou Lagoon, Côte d'Ivoire.…”
Section: Resultscontrasting
confidence: 94%
“…) is lower to the reported values ofMarthe et al, (2015) who recorded 19.2µg/L at Coastal Potou Lagoon, Côte d'Ivoire. ISSN 2250-3153 This publication is licensed under Creative Commons Attribution CC BY.…”
contrasting
confidence: 83%
“…(), Patel and Parikh () and Marthe et al . (). The DO concentration exhibited a positive correlation with pH and negative correlations with temperature, electrical conductivity, and BOD and total dissolved solids concentrations, a trend supported by Patel and Parikh ().…”
Section: Resultsmentioning
confidence: 97%